Desain Formulir Informed Consent Berbasis Elektronik Guna Menunjang Efektifitas Rekam Medis Elektronik - Mundok, Mohammad Syahrial; Sufyana, Candra Mecca; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Informed consent is a very important requirement for patients to guarantee the patient's right to obtain sufficient information before agreeing to medical procedures to be carried out on the patient. In the digital era, implementing electronic-based informed consent has become relevant to support electronic medical records. This research aims to make the informed consent form which was previously manual or paper digital, so that it is hoped that it can increase efficiency and accuracy in managing medical information, speeding up the administration process. , and increase patient involvement in decision making. The research data collection methods used include interviews, literature study, and observation with descriptive analysis. The system development method uses the waterfall method. It is hoped that the results of designing an information system using the selected method will make the performance of doctors and nurses more effective in preparing letters of approval for medical treatment or informed consent so that providing information is more efficient and data security is maintained. Apart from that, this information system is expected to be able to maximize service to patients and the quality of service in hospitals can increase.